PELATIHAN PENERAPAN PENCEGAHAN COVID-19 DALAM MENJAGA POLA HIDUP SEHAT MASYARAKAT KELURAHAN SEKARPUTIH - Agustin Wulan Suci Dharmayanti; Fajar Risqi Zaenulloh; Tecky Indriana; Dina Tsalis Wildana; Dwi Warna Aju Fatmawati; Lusi Hidayati (LP2M Universitas Jember, 2022)
Coronavirus is a new type of virus that originated in the Chinese city of Wuhan and infected almost all residents worldwide. Coronavirus has a good and bad impact on social life. One of the good effects is the reduced use of motorized vehicles and air pollution, but the bad impact that is caused is the bad effect, namely that many people have been affected by this pandemic, such as the middle- and lower-class people because the economic factor is one of the most important problems. The spread of this virus is not only limited to the physical but also impacts a person's psychology. We did community service activities in Sekarputih Village, Tegalampel District, Bondowoso Regency. The activities included surveying community needs, program planning, and implementation stages. One of the implementations of breaking the spread of Covid-19 was implementing a healthy lifestyle by utilizing the yard for planting toga plants (family medicinal plants) and providing information related to Covid-19 to the community. This activity was assisted by the RT.02 RW.01 Sekarputih Village community. In addition to this implementation, this activity is expected to prepare Sekarputih Village for the provincial-level radiant village and tough village competitions to represent Bondowoso Regency